Co-labore, une utopie d’avenir ? - Emmanuelle Reille-Baudrin (Perspectives Interdisciplinaires sur le Travail et la Santé)
Based on an activity co-analysis in a coworking space using a clinical psychology of work approach, this article reports on the precursory nature of this new form of work organization, and the motivations and objectives of the co-founders of this space and those of the coworkers who use it. As a concrete utopia, in the sense of Bloch, it offers people a purpose to work towards. For these disillusioned or unemployed professionals, coworking is invented and approached with a proactive consciousness, a creative tone, and a wish to change the world. To make work so as to succeed in living off of one’s work, to co-labor, to work alone in the presence of others when work and employment, in their wage form, have fled. Does coworking establish an adaptive alternative, a "dream with both feet on the ground ", a new paradigm, a utopia for the future?